On sustainable delta development: Sustainable coastal adaptation is possible - Water as catalyst for sustainable development - Jonkman, Bas; Ovink, Henk (Journal of Delta Urbanism, 2020)
The main ingredient of Delta Urbanism is the dialogue. The integration of concepts, ideas, language and measures can only be done through conscious exchange in continuous dialogue. This is not taken lightly, just exchange is not good enough, a solid dialogue is conscious and supported by methods that orchestrate steps, information and design. Therefore a section in which dialogue between two professionals is presented is essential to this journal. The exchange is directed through writing and editing, taking time to think responses through and position clearly in the dialogue. This issue represents the dialogue between Bas Jonkman and Henk Ovink who continue the dialogue that they started as keynote speakers at the conference of Delta Urbanism in times of climate crisis in March 2020.